Reduction of Zika virus infectivity in platelet concentrates after treatment with ultraviolet C light and in plasma after treatment with methylene blue and visible light. Issue 11 (17th July 2017) - Fryk, Jesse J.; Marks, Denese C.; Hobson‐Peters, Jody; Watterson, Daniel; Hall, Roy A.; Young, Paul R.; Reichenberg, Stefan; Tolksdorf, Frank; Sumian, Chryslain; Gravemann, Ute; Seltsam, Axel; Faddy, Helen M.
Abstract : BACKGROUND: Zika virus (ZIKV) has emerged as a potential threat to transfusion safety worldwide. Pathogen inactivation is one approach to manage this risk. In this study, the efficacy of the THERAFLEX UV‐Platelets system and THERAFLEX MB‐Plasma system to inactivate ZIKV in platelet concentrates (PCs) and plasma was investigated. STUDY DESIGN AND METHODS: PCs spiked with ZIKV were treated with the THERAFLEX UV‐Platelets system at 0.05, 0.10, 0.15, and 0.20 J/cm 2 UVC. Plasma spiked with ZIKV was treated with the THERAFLEX MB‐Plasma system at 20, 40, 60, and 120 J/cm 2 light at 630 nm with at least 0.8 µmol/L methylene blue (MB). Samples were taken before the first and after each illumination dose and tested for residual virus. For each system the level of viral reduction was determined. RESULTS: Treatment of PCs with THERAFLEX UV‐Platelets system resulted in a mean of 5 log reduction in ZIKV infectivity at the standard UVC dose (0.20 J/cm 2 ), with dose dependency observed with increasing UVC dose. For plasma treated with MB and visible light, ZIKV infectivity was reduced by a mean of at least 5.68 log, with residual viral infectivity reaching the detection limit of the assay at 40 J/cm 2 (one‐third the standard dose). CONCLUSIONS: Our study demonstrates that the THERAFLEX UV‐Platelets system and THERAFLEX MB‐Plasma system can reduce ZIKV infectivity in PCs and pooled plasma to the detection limit of the assays used. These findings suggest both systems have the capacity to be an effective option to manage potential ZIKV transfusion transmission risk.